Effectiveness of Using Simulation Method in Improving Post-Part Mothers’ Knowledge About Newborn Care At Bandung City Hospital in 2025 - Sri Hayati; Revita Nurmandasari; Maidartati Maidartati (International Journal Of Health Science, 2025)
One of the indicators of the Sustainable Development Goals (SDGs) is the reduction of the Neonatal Mortality Rate (NMR) by 2030. The highest mortality rate in newborns occurs within the first 24 hours after birth, which is often caused by inadequate newborn care. Health education is an important effort to address this problem. The selection of appropriate health education media plays a significant role in increasing maternal knowledge. One of the effective media is the simulation method, which presents real-life situations using props, enabling mothers to practice and understand newborn care in a more tangible way. This study aimed to determine the effectiveness of the simulation method in increasing maternal knowledge about newborn care at Bandung City Hospital. The research employed a pre-experimental design with a one-group pre-test–post-test approach. Data were collected using a newborn care knowledge questionnaire distributed via Google Forms. Univariate data analysis was conducted using percentages, while bivariate analysis was performed using the Wilcoxon Signed Rank Test. The findings showed that, in the pre-test stage, less than half of the respondents (46.7% or 14 mothers) had sufficient knowledge, while the rest had low knowledge levels. After the intervention, the post-test results indicated that the majority (90% or 27 mothers) had good knowledge. Bivariate analysis revealed a p-value of 0.001, indicating a statistically significant improvement in knowledge after the simulation-based health education. In conclusion, the simulation method proved to be effective in increasing postpartum mothers’ knowledge of newborn care. The findings suggest that health facilities should consider integrating simulation-based education into maternal and neonatal health programs to support the achievement of SDG targets related to reducing neonatal mortality.